2016
DOI: 10.1177/1053815116679414
|View full text |Cite
|
Sign up to set email alerts
|

Social Experiences of Children With Disabilities in Inclusive Portuguese Preschool Settings

Abstract: Based on peer sociometric reports, we examined how number of friendships, social acceptance, and characteristics of social networks vary as a function of disability profile. We also investigated teachers' awareness of the sociometric status of young children with disabilities.Participants were 86 children with disabilities (63 boys) enrolled in inclusive preschool classrooms from the Metropolitan Area of Lisbon, Portugal (Mage = 67.33 months, SD = 10.54).Findings suggest children with severe or socio-behaviora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 33 publications
(80 reference statements)
2
15
0
3
Order By: Relevance
“…Results showed that children without SN had higher social acceptance levels than their peers with SN on both fall and spring semesters. These findings are consistent with the results of the similar studies in the literature (Bakkaloğlu, Sucuoğlu, & Özbek, 2019;Buysse, Goldman, & Skinner, 2002;Ferreira et. al., 2017;Keane & Calkins, 2004;Koster, Pijl, Nakken, & Van Houten-van den Bosch, 2010;Mand, 2007;van der Wilt, van der Veen, van Kruistum, & van Oers 2019).…”
Section: Conclusion and Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Results showed that children without SN had higher social acceptance levels than their peers with SN on both fall and spring semesters. These findings are consistent with the results of the similar studies in the literature (Bakkaloğlu, Sucuoğlu, & Özbek, 2019;Buysse, Goldman, & Skinner, 2002;Ferreira et. al., 2017;Keane & Calkins, 2004;Koster, Pijl, Nakken, & Van Houten-van den Bosch, 2010;Mand, 2007;van der Wilt, van der Veen, van Kruistum, & van Oers 2019).…”
Section: Conclusion and Discussionsupporting
confidence: 93%
“…In our country, children with SN mostly start their education life in preschools within the scope of inclusion. Although different dimensions of inclusive education in preschools and primary schools have been examined (Aguiar, Moiteioro, & Pimentel, 2010;Baydık & Bakkaloğlu, 2009;Ferreira, Aguiar, Correia, Fialho, & Pimentel, 2017), it has not yet been examined whether attending inclusive preschools causes changes in the social acceptance of children with and without SN. Social acceptance of children with SN by their TD peers is an important variable both for achieving the positive effects expected from inclusion and supporting the development of children with SN.…”
Section: Summary Introductionmentioning
confidence: 99%
“…Improving physical fitness of children with special needs needs to be increased in doing physical activities and sports, therefore it takes an important role for adaptive physical education teachers in schools to increase physical activity and develop social relations in mentally disabled children and students in general (Ferreira, 2017)adaptive physical education teachers have a role important in improving the basic motion and mental health of retarded children through physical activity of students with modification games that are easy to do and generate excitement for students to improve physical fitness (Sumaryanti, 2013). Adaptive physical education teachers can design learning models according to the growth and development of children mental retardation in extraordinary elementary schools (Mansur, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…In order to select the results relevant to our target group, we took into account the information provided by the studies on the severity of the disability. Only one study (Dessemontet, Bless, & Morin, 2012) referred to standardised measures (IQ), while three other studies (de Graaf & de Graaf, 2016;de Graaf & van Hove, 2015;Ferreira, Aguiar, Correia, Fialho, & Pimentel, 2017) reported measures derived from non-standardised instruments (e.g. Abilities Index declared by teachers, IQ reported by parents, IQ in different areas declared by parents and teachers).…”
Section: Contexts Of Inclusion and Participantsmentioning
confidence: 99%
“…Looking at results around social interactions, three main topics emerged. Studies took into account the relationships between students with MSCD and their peers, such as contact during class activities (Ballard & Dymond, 2016;Feldman et al, 2016), friendships (Ballard & Dymond, 2016;Feldman et al, 2016;Ferreira et al, 2017;Harkins, 2013;Naraian, 2011;Olsson et al, 2018;Potter, 2014), and social acceptance by peers (Huck et al, 2010;Leyser & Kirk, 2011;Tuersley-Dixon & Frederickson, 2016), and teachers (Harkins, 2013). Feldman et al (2016) looked carefully at the opportunities for interaction during class activities between students with disabilities and their peers.…”
Section: Social Outcomesmentioning
confidence: 99%